(untitled) (Proceedings OPTIMAL, 2024)
Blood group is a blood grouping system that is based on the types of antigens that humans have. Blood type is very important information to reveal a more specific identity that has been granted since birth. Every individual has their own blood type. Blood type not only explains the type of blood owned by an individual, but can also explain his personality. From a psychological perspective, each blood type has differences in the formation of behavior and personality characteristics. Personality is the organization of attitudes that a person has as a background to behavior and determines a person’s personality. Personality is an integration of aspects, such as behavior, intelligence, talent, attitudes, motives, interests, abilities, morals, and physical aspects, if you have these aspects of personality such as high interest in learning, of course, it will tend to affect learning achievement. The purpose of this study was to determine the effect of blood type on student academic achievement conducted at the Almuslim University Midwifery Diploma III Program. This research method is descriptive statistical research. The population of this study were students of the Diploma III Midwifery Program with a sample size of 42 people using total sampling technique, data analysis using simple linear regression test. The results of the research univariate analysis are the characteristics of the majority of respondents aged 19 years (85.7%), the work of parents of farmers amounted to 16 (18.1%), graduates from high school 19 respondents (45.2%). This study shows the majority of respondents have blood type O with 22 (52.4%) respondents and the majority of respondents’ achievement is underachieving with 29 (69%) respondents. The results of bivariate analysis of simple linear regression test obtained Sig value (0.533) > 0.05. The conclusion of this study is that blood type has no effect on academic achievement, academic achievement is not only due to internal factors but also due to external factors.